Penerapan Teknik Level Angle Untuk Memperkuat Dramatik Dalam Penciptaan Film Fiksi “Genius Dari Syurga” - Febry Ayu Retno; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The final work of art creation entitled the application of the level angle technique to strengthen the drama in the cinematography of the fiction film "Genius From Heaven" is a work of fiction film that tells the story of a child who is being sued by his father. From a young age, Dino was required by his father to be smart, but Dino was lacking in that regard. Dino has his own advantages, from the age of 6 Dino had a hobby of playing the piano, but his father did not support him in that matter, until finally Dino was known as a professional piano player. The cinematography in the creation of the fictional film "Genius From Heaven" uses a level angle technique to strengthen the action so as to build drama that is better from a visual perspective. The aim is to provide the mood and reaction of the audience to follow the narrative flow in the film "Genius From Heaven".